Factors that influence intention to use recycled clothes among generation Z in Malaysia - Ang, How Ying; Lee, Zi Yang (2023)
Nowadays, the fashion industry has brought an ultimately negative impact towards the natural environment due to the fast change demand. The concept and consciousness on sustainability among fashion industry was raised and gradually improving. Recycled clothes as one of the sustainable products that can reduce the harmful to environment, are in a continuous growing phase in Malaysia. Generation Z, as the largest population group in Malaysia, is increasingly more aware to negative consequences of environment and might willing to use recycled clothes for the conservation of nature. Therefore, this study has examined factors that influence the intention to use recycled clothes among Generation Z in Malaysia. In this study, Value-Belief-Norm Theory (VBN) will be the main theory to determine the intention to used recycled clothes which includes 4 sections that comes with 7 variables, Altruistic Values (AV), Egoistic Values (EV), Biospheric Values (BV), Awareness of Consequences (AOC), Ascription of Responsibility (AOR), Personal Norm (PN), Intention to used recycled clothes (ITU). In addition, we have also integrated Theory of Planned Behaviour (TPB) 3 variables in to proposed framework which is Subjective Norms (SN), Attitude (ATT) and Perceived Behaviour Control (PBC). A total of 384 respondents of Malaysian Generation Z’s data has been collected through questionnaire. SmartPLS 4 software is applied in this study to analyse the data by conducting the measurement model and structural model, which will be used to investigate the relationship between these variables. According to the findings, all the hypotheses have a significant relationship that led to the intention to use recycled clothes in the context of Malaysia. This research can be beneficial to the researcher and practitioner to have more understanding the factors that influencing Malaysian Generation Z and take corresponding actions to enhance willingness of using recycled clothes.